2021
DOI: 10.1016/j.imr.2020.100705
|View full text |Cite
|
Sign up to set email alerts
|

Risk levels of herb-induced liver injury in Korea: from a meta-analysis

Abstract: Background As the use of herbal medicines increased worldwide, there has been concern about the risk of herb-induced liver injury (HILI). Many clinical studies have assessed the risk of HILI in Korea. Methods Therefore, we conducted a meta-analysis of the incidence of HILI in Korea, by analyzing nine clinical studies. These involved 8625 participants (3274 males; 5351 females), including 436 outpatients (three studies) and 8189 inpatients (six studies). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Host-dependent risk factors are related to the consumer of herbal products and include factors such as age, sex, alcohol consumption, and chronic liver disease [ 14 , 17 , 19 , 52 , 55 , 57 ].…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Host-dependent risk factors are related to the consumer of herbal products and include factors such as age, sex, alcohol consumption, and chronic liver disease [ 14 , 17 , 19 , 52 , 55 , 57 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In the USA, the opposite happens, with women being more frequently affected than men [ 19 ]. In Korea, one study pointed to a higher incidence in males than in females [ 57 ]. However, another study in Korea showed just the opposite trend, with females having higher HILI incidence [ 45 ].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation